2008
DOI: 10.1074/jbc.m706021200
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ Induces X-linked Inhibitor of Apoptosis-associated Factor-1 and Noxa Expression and Potentiates Human Vascular Smooth Muscle Cell Apoptosis by STAT3 Activation

Abstract: Interferon (IFN)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 52 publications
1
29
0
Order By: Relevance
“…28,32,33). Consistent with previous reports showing that IFNs transactivate Noxa in endothelial cells, primary macrophages, and various tumor cells through activation of IRF3 and 7 (20,24,34,35), our data show that IFNs upregulate Noxa expression by increasing the expression levels of IRF1, 3, and 7 in a p53-independent manner and that IRF4 can be substantially reduced by IFN-g possibly acting as a counter partner of IRF1, 3, and 7. It is also worth noting that IRF4, an addiction protein of multiple myeloma cells induced by c-myc (36), may allow tumor cells to survive by repressing Noxa expression.…”
Section: Discussionsupporting
confidence: 81%
“…28,32,33). Consistent with previous reports showing that IFNs transactivate Noxa in endothelial cells, primary macrophages, and various tumor cells through activation of IRF3 and 7 (20,24,34,35), our data show that IFNs upregulate Noxa expression by increasing the expression levels of IRF1, 3, and 7 in a p53-independent manner and that IRF4 can be substantially reduced by IFN-g possibly acting as a counter partner of IRF1, 3, and 7. It is also worth noting that IRF4, an addiction protein of multiple myeloma cells induced by c-myc (36), may allow tumor cells to survive by repressing Noxa expression.…”
Section: Discussionsupporting
confidence: 81%
“…Given the significantly reduced GVHD in both BMT settings, it appears that the increased expansion of Tregs as well as the attenuated Th1 differentiation trumped the reduced AICD. Furthermore, it is possible that IFN-γ-mediated suppression of Tregs is critically dependent on the presence of Stat1, whereas IFN-γ-dependent AICD of donor T cells may utilize Stat1-independent signaling pathways (57). In addition, the role of IFN-γ in regulating GVHD is influenced by conditioning intensity (13) and may further depend on the presence and intensity of allostimulation from host hematopoietic cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have observed that the mutant virus produces a large-plaque phenotype and have measured a higher induction of cell death in E95D-infected cells. Although generally considered to be antiapoptotic (3), STAT3 has been demonstrated to participate in the induction of apoptosis in specific situations and cell types (5,19). Considering that STAT1 targeting in the absence of STAT3 targeting would create an unusual situation for mumps virus, it seems reasonable to predict that more dramatic consequences would result from the E95D mutant virus in vivo if an appropriate model system were available.…”
Section: Discussionmentioning
confidence: 99%